Credit cycles and real activity - the Swiss case - Rolf Scheufele; Gregor Bäurle (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper analyzes credit supply and demand shocks for the Swiss economy. Using a medium scale BVAR model we are able to take into account various interactions of housing prices, credit supply and demand, interest rates and real activity measures. To identify meaningful economic shocks, we used a combination of zero and sign restrictions. Generally, the empirical analysis implies that the effects of credit supply and demand shocks on real activity are limited, only playing a substantive role in specific episodes. Furthermore, the credit supply shocks (i.e. bank lending shocks and monetary policy shocks) explain a large fraction of housing price and credit fluctuations. Indeed, they tend to be more important for housing prices than housing demand shocks. There is further evidence that shocks related to credit supply, monetary policy shocks dominate bank lending shocks. For Switzerland as a small open economy it turns out to be very crucial to take into account foreign demand which is able to explain a substantial variation in real and financial variables.
Keywords: C11; C32; E44; 330